Development of Customer Services Web-Based System - Mohammad, Adnan I. (2009)
The main objective in this study is to design web-based system for Plaza Low Yat Mall in Kuala Lumpur (KL) - Malaysia to serve the customers and help them to find suitable sales locations and offering best choices available, all through accessing a database designed for the mall since this system will have search options to find what they want. Also this system will explain and give other information about Plaza Low Yat Mall, as the Mall offer a huge variety of goods, its not easy for costumer always to find the best offer that fulfill their needs, otherwise, it would cost them long time to search, more efforts. This system will make the process much easier and give the best offer with less effort via browsing the database and search into it.